An innovative quasi-zero stiffness isolator with three pairs of oblique springs. (15th February 2021) - Zhao, Feng; Ji, Jinchen; Ye, Kan; Luo, Quantian
Highlights: An innovative QZS isolation system with three pairs of linear oblique springs. Small coefficient of the 3 rd order nonlinear term of the Taylor series of the stiffness. A wider QZS range with an almost horizontal line around the equilibrium position. lower resonance frequency and transmissibility than the system with one pair of oblique springs. Theoretical analysis with experimental validation for the proposed QZS system. Abstract: This paper presents an innovative design of the quasi-zero stiffness (QZS) isolator with three pairs of oblique springs. Formulations of stiffness are firstly derived and parameter study is then conducted to obtain an optimal design of the proposed isolator. The proposed isolator initially has five independent parameters. By imposing stiffness and its second order derivative to be zero at the static equilibrium position, there exist three independent parameters that can be optimised to design this type of QZS isolator. A distinctive feature of the proposed isolator is that there exists a nearly horizontal straight line near the equilibrium position in the stiffness curve as the nonlinear coefficient of the Taylor expansion up to the third order of the elastic force or the Duffing differential equation is very small; thus a wider QZS region with lower transmissibility can be achieved in the present isolator. Static and dynamic analyses are presented with focusing on dynamic response in terms of displacement transmissibility. A prototype is fabricated and tested to evaluate the proposed design. The experimental results validate the present formulations in static and dynamic analyses and show lower transmissibility as compared to the corresponding QZS isolator with one pair of oblique springs and the linear isolator. Graphical abstract: Image, graphical abstract